EFEKTIVITAS LAYANAN INFORMASI MENGGUNAKAN MEDIA AUDIOVISUAL UNTUK MENGURANGI PERILAKU MEROKOK PADA SISWA MTS AL-AZHAR KECAMATAN ALALAK KABUPATEN BARITO KUALA TAHUN PELAJARAN 2017/2018 - amalia, rizki; Hamzah, Hamzah; Fauzi, Zainal (UNIVERSITAS ISLAM KALIMANTAN, 2018)
The problem in this research is that there are some students who are known to have smoked in MTs Al-Azhar. The purpose of this study was to determine differences in the level of smoking behavior before and after students treated. The method used is experimental method with type pre-experimental design in the form of One Group Pretest-Posttest Design. The method of solving the problem is to provide information services using audiovisual media on the sample after the pre-test. The population is the entire class VIII MTs Al-Azhar and the sample is one class of 30 students. The sampling technique in this research is purposive sampling. Data analysis techniques used in this study are descriptive statistics and inferential statistics Wilcoxon test with the help of SPSS application version 22. Based on the results of descriptive analysis obtained pretest results of 37% and posttest of 32%. Then based on Wilcoxon test statistical analysis results with the help of SPSS 22 applications obtained Zhitung of -3.817 with 5% significance level of 0.05 and Asymp.Sig = 0,000. Because Asymp.Sig = 0.000 <0.05, Ha is accepted and Ho is rejected so it can be concluded that there is a significant difference of smoking behavior of grade VIII students of MTs Al Azhar Alalak Sub-district, Barito Kuala District in the year 2017/2018 between before and after given information service using audiovisual media.Â Keywords: Information Services; Audiovisual Media; Smoking Behavior